PENGARUH KOMPETENSI SUMBER DAYA MANUSIA DAN PEMANFAATAN TEKNOLOGI INFORMASI MELALUI KOMITMEN ORGANISASI TERHADAP KINERJA PEGAWAI KECAMATAN DI KOTA PEKANBARU - T. Ardi Dwisasti; Kusworo; Ruhana, Faria; Sutiyo (Faculty of Law, Universitas Pekalongan, 2024)
This study aims to analyze the influence of human resource (HR) competency and information technology (IT) utilization on employee performance, with organizational commitment as a mediating variable. This study was conducted on permanent employees within the Pekanbaru City District. The research method used was quantitative, with probability sampling using the Stratified Random Sampling technique, drawing 252 respondents from a population of 683. Data were collected through questionnaires and analyzed using Structural Equation Modeling (SEM) with Smart PLS. The results indicate that HR competency and information technology utilization have a direct and positive effect on employee performance. Furthermore, this study demonstrates that organizational commitment significantly mediates the effect of HR competency on employee performance and significantly mediates the effect of information technology utilization on employee performance. These findings indicate that employees with strong organizational commitment, demonstrated by professionalism, loyalty, and honesty, and who are able to utilize IT effectively and efficiently, will make a greater contribution to improving administrative service performance.